Vertical GaN-on-GaN Schottky Barrier Diodes With Multi-Floating Metal Rings - Tsung-Han Yang; Houqiang Fu; Kai Fu; Chen Yang; Jossue Montes; Xuanqi Huang; Hong Chen; Jingan Zhou; Xin Qi; Xuguang Deng; Yuji Zhao (IEEE Journal of the Electron Devices Society, 2020)
Vertical GaN Schottky barrier diodes (SBDs) with floating metal rings (FMRs) as edge termination structures have been fabricated on bulk GaN substrates. Devices with different FMR geometries were investigated including various numbers of rings and various spacings between rings. These devices have a low Ron of 1.16~1.59 mΩ·cm2, a turn-on voltage of 0.96~ 0.94 V, a high on-off ratio of 109, a nearly ideal ideality factor of 1.03~1.09, and a Schottky barrier height of 1.11~1.18 eV at room temperature. These devices have similar forward electrical characteristics, indicating that FMRs don't degrade the device rectifying performance. The ideality factor decreased and the Schottky barrier height increased with increasing temperature from 300 K to 420 K, where the temperature dependencies of the two parameters indicate the inhomogeneity of the metal/semiconductor Schottky interface. In addition, FMRs can improve device breakdown voltages. As the number of FMRs increased from 0 to 20, the reverse breakdown voltage increased from 223 to 289 V. As the spacing between the FMRs increased from 1.5 to 3 μm, the reverse breakdown voltage increased from 233 to 290 V, respectively. These results indicate multiple FMRs with proper spacings can effectively improve breakdown performance without degrading the device forward characteristics. This work represents a useful reference for the FMR termination design for GaN power devices.